Emergence of metachronal waves in a chain of symmetrically beating filaments - Narina Jung; Won Kyu Kim; Changbong Hyeon (Physical Review Research)
Recent experiments show that metachronal waves (MCWs) can emerge from a chain of symmetrically beating nematodes aligned at the edge of sessile droplets. Our study, employing a coupled elastohydrodynamic model of active filaments, elucidates that a misalignment caused by a tilt against the bounding wall disrupts the synchronization and generates a constant time lag between adjacent filaments, giving rise to MCWs. The MCWs, enhancing the fluid circulation, achieve their maximum thermodynamic efficiency over the same range of tilt angles observed in the nematode experiments.